(3QSGdI aj GdJhMjOs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbgGQ CeG HYO CjgG GdfGS EJbhG Gddg JYGdi hGYJUehG HGdbQBf hGdBKGQ hdG JchfhG cGdPjf HOdhG fYeg Gddg caQkG s
(3BNQgG (B:s
" (3dbO caQ GdPjf bGdhG Cf Gddg gh GdeSjM GHf eQje hbGd GdeSjM jG Hfi ESQGFjd EYHOhG Gddg QHi (B" (3Gddg CcHQ hSHMGf Gddg hdG Edg EdG Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B- (3NRGfI Bd HGTf CYjGf GdHUQI (B(26 (3C(B) s
Keywords: (3GdeLGejYs